Improvement of the Statement of Financial Results as an Information Base for Strategic Decision Making - T. Yu. Druzhilovskaya; E. S. Druzhilovskaya (Учёт. Анализ. Аудит, 2021)
The article presents the results of a study of the possibilities to improve approaches to generating a report on financial results as an information base for making strategic decisions. It critically analyses the significance of the changes in this report, stipulated by the draft federal accounting standard for the non-state sector “Financial statements of the organization” (FAS FS), which should come into force from 2021. The authors identify and systematize the main changes planned by the FAS FS draft in report on financial results formation, including not only adjusting certain articles, but also improving the approaches to the presentation of a number of indicators. The importance of each of these changes, their positive and negative significance for the persons making strategic decisions is determined; the main problematic and debatable issues to improve the formation of the report on financial results from the perspective of users of the reporting are identified. An example of the form of the report on financial results is provided, aimed at presenting the reliable and understandable information necessary for decision-making users. The results of the study can be useful to a wide range of readers interested in the problems of forming a report on financial results, and can also be applied in the practical work of the accounting departments of organizations, in the educational process of higher educational institutions and in the creation and improvement of relevant regulatory documents on accounting.